AN EXPERIMENTAL STUDY: IMPROVING STUDENTS’ VOCABULARY MASTERY BY USING ENGLISH SONGS - Rizky Gushendra (Indonesian Journal of Integrated English Language Teaching, 2017)
Based on the writer’s observation in teaching and learning process, the students had low achievement in vocabulary mastery in learning English. Memorizing vocabulary was not effective to achieve the students’ vocabulary because it was hard for the students to memorize it. So, to solve this problem, the writer used a strategy to improve the students’[ mastery in vocabulary. The strategy was using songs. The aim of this research was to find out a significant effect of using English songs to improve students’ vocabulary mastery. This research was a quantitative research by an experimental design. In this research, there were two classes as a sample, that classes were an experimental class and a control class. Variables in this research consisted of two variables. They were English songs as variable X and students’ vocabulary mastery as variable Y. The total number of population was 54 students, which were finally selected 40 students as sample of this study.  The sample was determined based on cluster sampling of an equal chance to be taken, regardless of their typical of groups. The result of the research showed that the students’ ability on vocabulary mastery test in experiment class was very good level, which was 82.25, and in control class was good level, which was 63.25. on the inferential analysis, the significant value was 0.000 higher than alpha 0.05, which meant the alternative hypothesis (Ha) was accepted. It means that using English songs can improve the students’ vocabulary mastery.